A case for the establishment of a legal framework within the Zimbabwean mining sector to effectively regulate the corporate and social responsibilistie of multinational social responsibilities of multinational corporations by Michelle Rufaro Maziwisa - Maziwisa, Michelle Rufaro (Department of Public Law, 2015)
Includes bibliographical references.